Developing a multilingual literary magazine in an English-only policy environment - Kasula, Alex Josef (BELT - Brazilian English Language Teaching Journal, 2017)
The following article discusses the development and outcomes of a multilingual literary magazine, Olowalu Review, within an English-only policy in the United States. First, there is a review of current literature surrounding the ideas of monolingual policies in the US (the context of the article) and current research of the theory of translanguaging for multilinguals and its practice thus far in English language learning classrooms (ELL). The article elaborates on the analysis of translanguaging from Kasula (2016) and how this analysis helps to promote multilingualism. Next, there is a discussion on the achievement of the initial objectives of Olowalu Review, and how this acted as a first potential step in creating a translanguaging space for multilinguals to express themselves and making change towards a more multilingual language policy.